Faith‑based organizations and the state: The challenges of development in Tanzania (Politeja, 2016)
Since Zanzibar and Tanganyika became the United Republic of Tanzania in 1964, African socialism called ujamaa spread widely in this country. The adoption of an African Socialist approach was accompanied by the nationalization of education and health facilities belonging to the religious institutions. However, since the collapse of ujamaa in the mid‑1980s, Tanzania saw the increased activity of various faith‑based organizations (FBOs) that were connected to the economic and political liberalization. The new system caused that FBOs have become part of a growing religious field which has repositioned itself toward the multiple opportunities and expectations of the established apex bodies to coordinate with each other and manage their relationships with the government. This article describes how religious actors in urban Tanzania have repositioned themselves in relation to the state as well as themselves during the liberalization era triggered by development.